Health Education on Risk Factors of Primary Dysmenorrhea and Anemia in Adolescent Girls at SMP Negeri 31 Padang - Lili Fajria; Ira Mulya Sari; Yelly Herien; Meri Neherta; Deswita; Vetty Priscilla; Hermalinda; Arif Rohman Mansur; Dwi Novrianda; Mutia Farlina; Wedya Wahyu; Yanti Puspita Sari (Warta Pengabdian Andalas, 2025)
Adolescence is a transition period from childhood to adulthood, where in adolescent girls it is marked by menstruation, breast enlargement, hips, and so on. As a result of these changes, adolescent girls are at risk of experiencing nutritional deficiencies in their bodies which can lead to anemia. Anemia is a condition where there is a lack of hemoglobin levels in the body, the impact of which will be seen now and in the future. Dysmenorrhea is also the most common disorder experienced by women, especially adolescents, during the menstrual cycle. Dysmenorrhea can have an impact on daily activities, but many adolescent girls still do not know the factors related to the occurrence of primary dysmenorrhea, so health education is needed. The purpose of this activity was to provide health education about the risk factors for primary dysmenorrhea and anemia in adolescent girls and to conduct Hb level checks. This community service activity was carried out by providing education with slides and videos related to the risk factors for primary dysmenorrhea and anemia in 100 female students at SMP N 31 Padang. Adolescents will complete a knowledge and attitude questionnaire regarding anemia and primary dysmenorrhea before and after the intervention. The results of this activity showed an increase in knowledge and attitudes of adolescent girls regarding the risk factors for primary dysmenorrhea and anemia. The results of Hb examinations in adolescent girls found that 6% of adolescent girls had anemia. It is hoped that this health education can be carried out periodically so that young women can have the right knowledge and a positive attitude in dealing with problems such as dysmenorrhea or anemia.